2017
DOI: 10.1111/eip.12432
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition and the course of social functioning in first‐episode psychosis

Abstract: These unexpected findings fail to align with previous research that has documented a more robust relationship between these 2 constructs, and raise critical questions with regard to the nature of the association between social cognition and social functioning among individuals with first-episode psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…However, they are not considered a unitary construct encompassing two different domains, diminished expression including alogia and blunted affect, and avolition-apathy referring to experiential deficits, including asociality, avolition and anhedonia [19][20][21], that have been consistently replicated regardless of the measurement instrument used [22][23][24]. Negative symptoms are present in the prodromal and initial stages of the disease, are persistent, worsen with age [9], behave independently of cognition or affectivity [25], present a lack of response to pharmacological treatment [26], and importantly, are the most distressing for the family and the main determinants of impairment in functioning and quality of life, which have now become the main therapeutic targets in people with schizophrenia [27][28][29] both in early and chronic stages [8,27,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…However, they are not considered a unitary construct encompassing two different domains, diminished expression including alogia and blunted affect, and avolition-apathy referring to experiential deficits, including asociality, avolition and anhedonia [19][20][21], that have been consistently replicated regardless of the measurement instrument used [22][23][24]. Negative symptoms are present in the prodromal and initial stages of the disease, are persistent, worsen with age [9], behave independently of cognition or affectivity [25], present a lack of response to pharmacological treatment [26], and importantly, are the most distressing for the family and the main determinants of impairment in functioning and quality of life, which have now become the main therapeutic targets in people with schizophrenia [27][28][29] both in early and chronic stages [8,27,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as commented above, a recent study found that social cognition acts as a mediator between cognitive reserve and global functioning, and also between verbal memory and global functioning ( 46 ). However, in another study ( 30 ) there were no longitudinal associations between social cognition at baseline and any measure of social functioning at 6-month follow-up. These results held both with and without corrections for multiple comparisons.…”
Section: Resultsmentioning
confidence: 88%
“…This point has been partially consistent with the results of our review. A study ( 34 ) applied an optimal statistical analysis for testing causality, and observed that baseline social cognition impairment led to worse real-world functioning in a 12-month follow-up; however, another two studies ( 29 , 30 ) did not find such a relationship, one of them find some cross-sectional associations but it did not test for in the follow-up ( 29 ), and the other ( 30 ) did not find significance for the longitudinal associations. In addition, some authors have suggested that social cognition would play a mediating role in between neurocognition and outcomes of social functionality, which would underline its importance from a clinical point of view, especially when detecting a first episode and undertaking early intervention ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for these inconsistencies is that the relationship between social cognition and social functioning is mainly accounted for by other factors. For instance, one study showed that the association between measures of social cognition and social functioning disappeared when neurocognition was controlled for (Woolverton et al, 2018). Based on these findings it is argued that, although a link between a traditionally-measured social functioning and social cognition was established, the lack of subjective, ecologically-valid perspective prevents it from being clinically and mechanistically relevant.…”
Section: Social Cognition: a Prerequisite For Social Functioning?mentioning
confidence: 99%